2011
DOI: 10.1038/nmat2936
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of electronic friction on Nb films in the superconducting state

Abstract: Investigations on the origins of friction are still scarce and controversial. In particular, the contributions of electronic and phononic excitations are poorly known. A direct way to distinguish between them is to work across the superconducting phase transition. Here, non-contact friction on a Nb film is studied across the critical temperature TC using a highly sensitive cantilever oscillating in the pendulum geometry in ultrahigh vacuum. The friction coefficient Γ is reduced by a factor of three when the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
175
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(189 citation statements)
references
References 24 publications
11
175
2
1
Order By: Relevance
“…This ad hoc damping, which can be motivated and derived from quite rigorous linear response treatments, reflects the direct coupling of the point particle to phonons and potentially electronic degrees of freedom of the substrate. 16,20,21 Most theories focus on the overdamped limit (e.g., by choosing the unit of time to be 1/γ and then sending m to 0), partly because this facilitates the solution of analytical theories. Conversely, AFM tips do not seem to be overdamped.…”
Section: Modelmentioning
confidence: 99%
“…This ad hoc damping, which can be motivated and derived from quite rigorous linear response treatments, reflects the direct coupling of the point particle to phonons and potentially electronic degrees of freedom of the substrate. 16,20,21 Most theories focus on the overdamped limit (e.g., by choosing the unit of time to be 1/γ and then sending m to 0), partly because this facilitates the solution of analytical theories. Conversely, AFM tips do not seem to be overdamped.…”
Section: Modelmentioning
confidence: 99%
“…More polarizable adsorbates like nitrogen, krypton and xenon are instead found to be completely pinned to lead below 10 K [129]. A convincing confirmation of electronic friction and of its suppression in the superconducting state is provided by non-contact friction measurements on niobium films carried out across the critical temperature using a highly sensitive cantilever oscillating in the pendulum noncontact geometry in ultrahigh vacuum [130]. The friction coefficient drops by a factor between 2 and 3 when the sample enters the superconducting state (see Fig.…”
Section: Electronic Magnetic Exotic and Quantum Frictionmentioning
confidence: 95%
“…Nevertheless, the details of the nonequilibrium atomic process are still vague because the friction interface is difficult to access experimentally. Recent sophisticated nanoscale experiments by atomic force microscopy (AFM) have shed light on the energy dissipation process [9][10][11][12][13][14][15][16]. For example, Saitoh et al measured the noncontact friction between solids and an AFM probe under high vacuum and observed a significant maximum value at a distance of a few nanometers between them [10].…”
Section: Introductionmentioning
confidence: 99%
“…Cannara et al performed a unique AFM experiment to compare the frictions between silicon surfaces with hydrogen and deuterium absorbates and suggested that the friction exhibits an isotopic effect due to the modification of phonon energy dissipation; however, a molecular dynamics (MD) simulation did not support their suggested mechanism [11,12]. Some researchers have studied the superconducting transition of a metal sample to distinguish the electronic contribution to the kinetic friction [10,[13][14][15]. Such a modern view that comprehensively addresses the friction as a nonequilibrium atomic phenomenon has identified remarkable features of the friction, but these investigations are still few in number.…”
Section: Introductionmentioning
confidence: 99%